Analisis Faktor Faktor Yang Mempengaruhi Preferensi Konsumen Terhadap Keputusan Pembelian Sagu Kasbi (Brand Sagu Jay) - Nurdiyanawati Djumadil; Suhardi Suhardi (Universitas Khairun, 2021)
The research identifies factors influencing consumer preferences of kasbi sago (Sagu Jay Brand) purchasing decision. It conducts in Ternate from July to December 2020. The kasbi sago from Sagu Jay Brand is produced in Jaya Village, distributed through collectors, and marketed in Ternate City. The brand is chosen because the village is a center of Sagu Jay sales with the highest consumer demand in North Maluku compared to other kasbi sago production. The research is a survey research using qualitative and quantitative methods. The qualitative aims at identifying research descriptions derived from traders in marketing the Sagu Jay product and related respondents. The qualitative data are then quantified by processing the data to generate tabulated valid data. The quantitative data are numeric or values in the variable are expressed in real numbers (Sugiono, 2014). Research variables to be observed include cultural, price, flavor, and purchase location factors. Consumer preference sampling refers to experts’ opinion that sampling used to obtain representative data is a non-probability sampling, namely accidental sampling. The research analysis method used is conjoint analysis. The research results of factors influencing consumer preferences of Sagu Jay purchasing decision in Ternate indicate that flavor factor at the original level (1.921) and the chocolate level (1.668) are dominant factors and levels that form consumer preferences. The second dominant factor is the texture factor at the dry level (0.918) followed by the price factor at the level of Rp. 10.000 (0.576), and purchase location factor at the level of Pasar Kota Baru (0.060). The lowest factor is cultural factors at regional acceptability (0.29). This suggests that the consumers prefer kasbi sago products from the Sagu Jay brand due to the flavor factor at the dry level than other factors.